Game On, Harmony On: Menjaga Keseimbangan Rumah Tangga di Era Hiperkoneksi Game Online Melalui Nasihat Imam al-Ghazali - Nurul Muslimah; Rahmat Ramadhan. MZ (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the past few decades, the electronic gaming industry has become a part of daily life. More and more people, including family members within a household, engage in playing games as a form of entertainment or recreational activity. One of the negative impacts of gaming is addiction. If someone becomes addicted to games, they may spend excessive amounts of time playing, neglecting their responsibilities and obligations at home. This research is conducted with the aim of examining how to maintain household balance in the era of hyperconnected online gaming through the advice of Imam al-Ghazali. The research methodology involves literature review analysis and data obtained from internet sources and literature, which are then analyzed textually. The findings of this research indicate that maintaining household balance in the era of hyperconnected online gaming can be achieved through the advice of Imam al-Ghazali, such as applying principles of responsibility, compassion, understanding, and effective communication to maintain balance in household interactions. This research is expected to contribute to the study of Islamic family law, providing insights for those involved in understanding how to maintain household balance in the era of hyperconnected online gaming.